2018
DOI: 10.1177/0894439318794412
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Heuristics That (Could) Fit: Information Search and Communication Patterns in an Online Forum of Investors Under Market Uncertainty

Abstract: This article examines information-search heuristics and communication patterns in an online forum of investors during a period of market uncertainty. Global connections, real-time communication, and technological sophistication have created an unpredictable market environment. As such, investors try to deal with semantic, strategic, and operational uncertainty by following heuristics that reduce information redundancy. In this study, we have tried to find traces of cognitive communication heuristics in a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The first is intuitive and heuristic, and the second is deliberative and analytic (Evans, 1984; Wason & Evans, 1974). Heuristic processing requires less cognitive effort and resources, whereas systematic processing requires comprehensive judgment (Casnici et al, 2019; Chaiken, 1980). Scholarship has revealed that although systematic processing produces enduring attitudes and a better understanding of complicated problems, people often prefer heuristic processing and strategies to conserve cognitive effort unless motivated by powerless status or increased emotion (Ebenbach & Keltner, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first is intuitive and heuristic, and the second is deliberative and analytic (Evans, 1984; Wason & Evans, 1974). Heuristic processing requires less cognitive effort and resources, whereas systematic processing requires comprehensive judgment (Casnici et al, 2019; Chaiken, 1980). Scholarship has revealed that although systematic processing produces enduring attitudes and a better understanding of complicated problems, people often prefer heuristic processing and strategies to conserve cognitive effort unless motivated by powerless status or increased emotion (Ebenbach & Keltner, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has shown that when facing relatively well-structured problems, decision makers tend to economize on cognitive resources by relying, even unintentionally, on framing effects, such as opinions of relevant others or defensive routines (Simon 1973;Levinthal and Rerup 2006;Kheirandish and Mousavi 2018). When problems are ill-structured, decision makers tend to follow adaptive heuristics by exploiting experience and analogies that reduce strategic and operational uncertainty into a coherent 'problem-space' -to paraphrase Nevel and Simon (1972; see also Goel 1992;Casnici et al 2019).…”
Section: Introductionmentioning
confidence: 99%